Comparison of Efficacy of H-File and ProTaper for Removal of Gutta-Percha from Root Canal in Non-Surgical Endodontic Retreatment: An in-vitro Study - Amin, Sadia; Ahmed, Alia; Awan, Amina; Awan, Fatima; Sajid, Khadija (Biological and Clinical Sciences Research Journal, 2025)
Effective removal of root canal filling materials is critical for successful endodontic retreatment. Various instrumentation systems have been developed to optimize gutta-percha removal. Among them, hand files such as Hedström (H) files and rotary systems like ProTaper Universal Retreatment files are commonly used. Objective: To compare mean percentage of total root canal filling material remaining between H-files and Pro Taper universal retreatment rotary system extracted teeth with root canal fillings. Study Design: Randomized controlled trial. Place and Duration of Study: Department of Operative Dentistry, Islamic International Dental Hospital, Islamabad from 30th September 2024 to 29th March 2025. Methodology: Sixty extracted single-rooted teeth were divided into two groups (30 each for H-file and ProTaper). After access cavity preparation and working length determination, canals were shaped up to a size 40 K-file using the step-back technique. Irrigation was done with 1% sodium hypochlorite, saline, and 17% EDTA, then obturated using gutta-percha and zinc oxide eugenol sealer. The teeth were stored at 37°C in 100% humidity for 30 days. After decoronation, the teeth were randomly assigned to either the H-file group or the ProTaper group. Retreatment began with gutta-percha removal using Gates Glidden drills and xylene, followed by retreatment with the respective systems. Roots were sectioned and examined under a 100xmicroscope, and images were analyzed with AUTOCAD software. Statistical analysis was done with the use of SPSS software, version 22.0. Descriptive statistics (mean and standard deviation) were calculated to assess the amount of residual gutta-percha in the canals of both experimental groups (H file and ProTaper). Results: The Shapiro-Wilk normality test revealed that the distribution of the amount of remaining gutta-percha in Group A (H files) and Group B (ProTaper) was not normal. The p-values were 0.039 for Group A and 0.045 for Group B—both less than the 0.05 level—indicating that the data are not normally distributed in either group. The results showed a statistically significant difference in the amount of the remaining gutta-percha after retreatment with H files (Group A) and ProTaper files (Group B). Group A (H files) had a significantly lower mean rank of 16.65, while Group B (ProTaper) had a higher mean rank of 44.35. This reflects that samples treated with H files had significantly less gutta-percha than the samples instrumented with the rotary ProTaper system. The sum of ranks also reflected this difference, being 499.50 for Group A and 1330.50 for Group B. Conclusion: In conclusion the ProTaper file-instrumented specimens (Group B) had significantly higher mean ranks compared to the H file-treated specimens (Group A), indicating that H files were more effective in removing gutta-percha from the root canal system (p < 0.001).